ANALISIS PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN RABBANI DI PEKANBARU - Eza Aprilia Sari; Sri Restuti; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyzed Brand image, Product quality on Purchasing decisions and Consumer satisfaction, research applied on consumer Rabbani in Pekanbaru. This research consists of four variabel: the dependent variabel, one intervening variable and two independent variables. They are Consumer satisfaction (Y2), Purchasing decisions (Y1), Product quality (X2), and Brand image (X1). This research was conducted with purposive sampling method on respondents who meet the criteria to fill in the questionnaire. In terms of data analysis, this research used path analysis method using SPSS (Statistical package for social science) version 21. Based on the hypothesis test conducted, results showed that research Brand image and Product quality significant and positive effect on Purchasing decisions, Product quality and Purchasing dicisions significant and positive effect on Consumer satisfaction. Whil Brand image positive and Purchasing decisions is not significant effect on Consumer satisfaction. Brand image and Product quality influence Consumer satisfaction are moderated by Purchasing decisions.Keywords: Brand image, Product quality, Purchasing decisions and Consumer satisfaction.